2018
DOI: 10.5194/angeo-36-459-2018
|View full text |Cite
|
Sign up to set email alerts
|

Wavenumber-4 structures observed in the low-latitude ionosphere during low and high solar activity periods using FORMOSAT/COSMIC observations

Abstract: Abstract. The main purpose of this study is to investigate the four-peak structure observed in the low-latitude equatorial ionosphere by the FORMOSAT/COSMIC satellites. Longitudinal distributions of NmF2 (the density of the F layer peak) and hmF2 (ionospheric F2-layer peak height) averages, obtained around September equinox periods from 2007 to 2015, were submitted to a bi-spectral Fourier analysis in order to obtain the amplitudes and phases of the main waves. The four-peak structure in the equatorial and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In the present study, both have downward phase propagation from lower heights indicating that the tides have source in the lower atmosphere. Recently, Onohara et al () suggested that the wave number 4 signature in the ionosphere can be due to the combination of DE3, stationary planetary wave (SPW) of wave number 4 with migrating tides. Earlier, Oberheide et al () revealed that SE2 and SPW4 could also form wavenumber 4 signatures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both have downward phase propagation from lower heights indicating that the tides have source in the lower atmosphere. Recently, Onohara et al () suggested that the wave number 4 signature in the ionosphere can be due to the combination of DE3, stationary planetary wave (SPW) of wave number 4 with migrating tides. Earlier, Oberheide et al () revealed that SE2 and SPW4 could also form wavenumber 4 signatures.…”
Section: Discussionmentioning
confidence: 99%
“…From the Table 1, the amplitudes of Wavenumbers 1 and 2 components are generally greater than Wavenumbers 3 and 4. Even so, only Wavenumbers 3 and/or 4 structures have been widely investigated (e.g., Chang et al, 2013; Fang et al, 2009; Immel et al, 2006; Jin et al, 2008; Onohara et al, 2018; Pedatella et al, 2012; Ren et al, 2009; Sagawa et al, 2005; Wang et al, 2015; Xiong & Lühr, 2013). Why the previous researchers did not put too much attention into the Wavenumbers 1 and 2?…”
Section: Discussionmentioning
confidence: 99%
“…However, some exclusive studies (e.g., England et al, 2006; Fang et al, 2009; Hagan et al, 2007; Jin et al, 2008; Ren et al, 2009; Wan et al, 2008) suggested that the Wavenumber 4 structure is due to the dynamo action of the eastward propagating diurnal tide of wave number 3 (DE3), which is mainly excited by the latent heat released in the tropical troposphere (Hagan & Forbes, 2002). Besides, some other factors, such as the semidiurnal nonmigrating tides of zonal wave number 2 (SE2), stationary planetary wave number 4 (SPW4) (e.g., T. Chen et al, 2019; Oberheide et al, 2011; Onohara et al, 2018; Pedatella et al, 2012), may also produce the Wavenumber 4 structure in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…When viewed at quasi-fixed local time (LT) from slowly precessing satellites, this feature manifests as a 4-peak longitude structure. Subsequent studies examined the LT and seasonal variations of related WN4 and WN3 structures (e.g., Ren et al, 2009), and investigated the underlying mechanisms in further depth (e.g., Maute et al, 2012;Mukhtarov & Pancheva, 2011;Oberheide et al, 2011;Onohara et al, 2018).…”
Section: Plain Language Summarymentioning
confidence: 99%